Treading Water: Tools to Help US Coastal Communities Plan for Sea Level Rise Impacts - Smith, Emily A.; Sweet, William; Mitchell, Molly; Domingues, Ricardo; Weaver, Christopher P.; Baringer, Molly; Goni, Gustavo; Haines, John; Loftis, J. Derek; Boon, John; Malmquist, David (Frontiers in Marine Science, 2019)
As communities grapple with rising seas and more frequent flooding events, they need improved projections of future rising and flooding over multiple time horizons, to assist in a multitude of planning efforts. There are currently a few different tools available that communities can use to plan, including the Sea Level Report Card and products generated by a United States. Federal interagency task force on sea level rise. These tools are a start, but it is recognized that they are not necessarily enough at present to provide communities with the type of information needed to support decisions that range from seasonal to decadal in nature, generally over relatively small geographic regions. The largest need seems to come from integrated models and tools. Agencies need to work with communities to develop tools that integrate several aspects (rainfall, tides, etc.) that affect their coastal flooding problems. They also need a formalized relationship with end users that allows agency products to be responsive to the various needs of managers and decision makers. Existing boundary organizations can be leveraged to meet this need. Focusing on addressing these needs will allow agencies to create robust solutions to flood risks, leading to truly resilient communities.